2016
DOI: 10.1016/j.ejps.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Critical material attributes (CMAs) of strip films loaded with poorly water-soluble drug nanoparticles: I. Impact of plasticizer on film properties and dissolution

Abstract: Recent studies have demonstrated polymer films to be a promising platform for delivery of poorly water-soluble drug particles. However, the impact of critical material attributes, for example plasticizer, on the properties of and drug release from such films has yet to be investigated. In response, this study focuses on the impact of plasticizer and plasticizer concentration on properties and dissolution rate of polymer films loaded with poorly water-soluble drug nanoparticles. Glycerin, triacetin, and polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Steiner et al (2016) also observed brittleness in poorly water-soluble drug nanoparticle-loaded films with similarly high drug loading using a lower molecular weight grade of HPMC as film-forming polymer. Although it may be possible to push the maximum drug particle loading in films above 45–50 wt% while maintaining acceptable film mechanical properties with more thorough formulation development, such as modulation of plasticizer content (Krull et al, 2016b), these results suggest that film brittleness is a major hurdle to overcome to achieve higher drug particle loadings in strip films for practical use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steiner et al (2016) also observed brittleness in poorly water-soluble drug nanoparticle-loaded films with similarly high drug loading using a lower molecular weight grade of HPMC as film-forming polymer. Although it may be possible to push the maximum drug particle loading in films above 45–50 wt% while maintaining acceptable film mechanical properties with more thorough formulation development, such as modulation of plasticizer content (Krull et al, 2016b), these results suggest that film brittleness is a major hurdle to overcome to achieve higher drug particle loadings in strip films for practical use.…”
Section: Resultsmentioning
confidence: 99%
“…Various particle engineering techniques have also been employed to improve poorly water-soluble drug dissolution rate for incorporation into strip films. These include wet stirred media milling (WSMM) (Davé et al, 2014; Krull et al, 2017; Krull et al, 2016a; Krull et al, 2016b; Krull et al, 2015; Sievens-Figueroa et al, 2012a; Susarla et al, 2015; Susarla et al, 2013) and high pressure homogenization (Lai et al, 2015; Shen et al, 2013) to reduce drug particle size, as well as liquid antisolvent precipitation (Beck et al, 2013) and melt emulsification (Bhakay et al, 2016) to produce drug nanoparticles via bottom-up approach. However, one perceived limitation shared by all means of incorporating poorly water-soluble drug into films is the existence of an inherent limitation on drug loading (Borges et al, 2015b; Dixit and Puthli, 2009; Hoffmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, drying is generally perceived as a stabilization step for nanocrystals to avoid typical deterioration occurring in a liquid nanosuspension, such as Ostwald ripening, particle aggregation, sedimentation, and creaming [ 56 , 57 ]. For all the aforementioned reasons, drug nanosuspensions have been dried, as illustrated in Figure 1 , via spray drying [ 33 , 34 , 58 , 59 , 60 , 61 , 62 ], fluid bed coating/granulation/drying [ 8 , 60 , 63 , 64 , 65 , 66 ], spray-freeze drying [ 7 , 67 ], freeze drying [ 68 , 69 , 70 , 71 , 72 ], vacuum drying [ 73 , 74 ], nanoextrusion [ 75 , 76 , 77 , 78 ], and wet casting–drying [ 40 , 79 , 80 , 81 , 82 , 83 ]. Drying processes convert drug nanosuspensions into nanocomposites that encapsulate or carry drug nanoparticles and their clusters dispersed as a secondary phase in the matrix of dispersants (stabilizers used in nanosuspensions and other excipients).…”
Section: Introductionmentioning
confidence: 99%
“…A plasticizer or intermolecular association would result in a higher free volume than that expected from ideal mixing, leading to higher molecular mobility and a lower T g value [26]. The impact of SLS on the T g of the bufadienolide nanosuspension with constant CCS can be seen in Figure 6(c-e), where decreasing concentrations of SLS led to a clear increase in T g , a trend that has been observed for multiple polymer-surfactant combinations [27,28]. These findings indicate that bufadienolides can be incorporated into a…”
Section: Thermal Properties Of the Optimized Formulationsmentioning
confidence: 69%